DOUBLE TRACK PROGRAM: EXTRACURRICULAR IMPLEMENTATION TO INCREASE SKILL IN VOCATIONAL HIGH SCHOOL - Santosa, Joko Budi; Santosa, Budi; Tentama, Fatwa (Journal of Vocational Education Studies, 2019)
The research was conducted aimed at knowing the effectiveness of the double track program model applied to secondary school education in Cilacap Regency. The dual track program model in question is a learning model that provides facilitation to high school students who will continue to college and also students who will look for work after graduating from school. This research was based on the number of high school graduates who do not go to college. There were 70% of students in the place of a study carried out students prefer to find work rather than continuing to college. This study uses the research and development (R & D) method developed by Borg & Gall and modified by Nana Syaodih Sukmadinata (2011), which consists of preliminary, development and testing stages. This research was conducted at Adipala 1 Public High School, Cilacap Regency. Study at the research stage is the initial condition of research where the school has implemented vocational skills learning, then continued with the development stage by providing soft skills training. Furthermore, this research was carried out by testing the Focus Group Discussion (FGD) method by a team of experts from educational practitioners with respondents from several school principals, and the teacher in charge of the program. The results of research and development found that according to the perceptions and opinions of education experts who are members of the focus group discussion (FGD) showed that the dual track program provides maximum service to students on two choices after graduating from school whether they want to go to college or seek employment. The dual track program also provides increased student competency in vocational skills learning and soft skills competencies.